Aesthetic perceptions and ethical valuations concerning to daily use o f the musical Instruments in the Ancient Greece (Iter, 2022)
I propose an approach on the ethical and aesthetic cultural treatment given by the ancientGreeks to the ir musical instruments (in this article. the focus of attention is on the aulós and thelyra). Diverse symbolisms (of ethical and aesthetic character) associate with distinct socialsituations. so that the meaning attributed to the aulós or to the lyra is not ahvay-s the same: oneis the meaning attributed to the aulós in the erotic context of the banquet. another one is itsmeaning in the accompaniment of an athletic or military activity: one is the meaning attributedto the lyra in the educational sphere. another one is its meaning in the funeral imaginary.Amongst the plurality of symbolic contexts. I herein choose to approach one of them: thedichotomy between the lyra and the aulós. in a pedagogical. moral, philosophical andmythological context. which leads us onto a deep symbolic level. which leads us to the oppositepair "culture na ture . This study takes us to a number of possi ble interpretations on identity.memory and ethnicity. Therefore. we shall perceive "beauty" as defining of identity processes.as well as organizer of social memory and ethnic register.
Keywords: The Ancient Classical World - Ancient Greece - Beauty - Musical instruments